Complementaty and alternative medicine precautions and potential risk and drug interactions in oral and maxillofacial surgery, periodontics and surgical dentistry - Nicholoff, T. J., Jr (The Journal of the Philippine Dental Association)
Health and wellness have become important positive lifestyle goals among the general populace in recent years, encompassing not only the promotion of health and well being, but the prevention and management of illnesses as well. A large part of health & wellness is "self care" oriented and may make use of homeopathic, botanical, nutriceutical products and herbal medicines,which may fall within the realm of Complementary and Alternative Medicine or CAM. Statistical studies demonstrate that a large part of the world's population use some form of CAM. Complementary & Alternative Medicine (CAM) runs the gamut from Herbal Medicine, Nutrition, Vitamins & Dietary Supplements, Mind-Body Medicine, to Alternative Healthcare Practices such as Traditional Chinese Medicine (TVM), Chiropractic, Ayurvedic Medicine and Homeopathy. Once considered "on the fringe" and "quackery", in recent years, some aspects of CAM have gained a degree of respectability and have been integrated into mainstream or conventional medicine and CAM can now be found on the curriculums of some of the most prestigious medical schools in the United States and Europe. (Perlman A; Wetzel MS, et al)